Indigenous Self-Discovery: “Being Called to Witness” - Koptie, Steven W. (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2010)
This paper presents a reflective topical narrative in a style this author described in researching Irihapeti Ramsden (2003), an Ngai Tahupotiki (Maori) nursing instructor of Aotearoa (New Zealand). It is a reflection on the nature of Indigenous scholar’s inquiry, or what Irihapeti Ramsden recognized as an often melancholic journey of self-discovery. It is an attempt to understand how, where, and why colonization has reduced us to dependent remnants of the self-reliant and independent peoples our stories remember. We are collectively creating an alternative voice to colonial lies/myths and calling for the restoration of the human dignity stolen along with lands, resources and human rights. Irihapeti Ramsden (2003) used her own melancholic journey of self-discovery to re-ignite trust and reciprocity between people, and to bring the idea of Cultural Safety to colonial New Zealand, thereby establishing a splendid map for future generations of all spaces in need of decolonization. She was met with considerable resistance in her homeland as she raised awareness of the truth about abuses of power by colonial institutions and bureaucracies. By similarly nagging in often difficult processes of self-discovery Indigenous scholars everywhere are helping to unravel a global inheritance of colonial practice. Reconciliation will only be possible when citizens honour Indigenous people’s resistance, resentment and rebellion to European myths of conquest. Indigenous scholars are Being Called to Witness seven generations and to preserve the beauty and strength our ancestors wanted to protect. Our ancestors scarified a great deal, and we must wipe our tears, open our eyes, listen deeply, clear our throats, and raise our strong voices to bear witness to our ancestors’ prayers.